Al-Futūr al-Rūḥī in the Qurʾān: A Semantic-Field Model of Spiritual Weakening - Mohammed Zabidi, Ahmad Fakhrurrazi; Jumat, Nur Huraidah Binti; Majid, Latifah Binti Abdul (UIN Sunan Kalijaga Yogyakarta, 2026)
Contemporary Muslim discussions often describe spiritual exhaustion (al-futūr al-rūḥī) alongside modern “burnout,” yet Qur’anic studies rarely examine how the Qur’an itself differentiates movements of spiritual weakening through its moral-psychological vocabulary. This article investigates how Qur’anic semantics articulate al-futūr al-rūḥī as a structured process rather than a loose set of moral descriptors. Using an integrated thematic approach combining semantic-field mapping with thematic exegesis, the study traces five interrelated roots—ghaflah(heedlessness), iʿrāḍ (turning away), nufūr (aversion), futūr (slackening), and kasl (ritual apathy)—and tests their relations through corpus retrieval, contextual disambiguation, and close reading of anchor loci across Makkan–Madinan contexts. Readings are constrained through classical tafsīr triangulation (al-Rāzī, Ibn Kathīr, al-Ālūsī, and Ibn ʿĀshūr) to avoid collapsing believer fluctuation into condemnatory categories directed at entrenched rejection or hypocrisy. The findings show a recurrent semantic progression from attentional dulling to volitional withdrawal, affective recoil, and outward slackening, with kaslfunctioning as an exegetically restricted boundary-marker rather than a default label for fatigue. The article further identifies Qur’anic counter-orientations within the same discourse (dhikr/tadabbur, tawbah, sujūd/khushūʿ, istiqāmah/ikhlāṣ, and shukr) that frame recovery as a cyclical reorientation. Overall, the study offers a text-grounded model that clarifies degrees and limits of al-futūr al-rūḥī in the Qur’an and provides a disciplined vocabulary for discussing spiritual fatigue without semantic overreach.